Abrigo de la Quebrada Level IV (Valencia, Spain): Interpreting a Middle Palaeolithic Palimpsest from a Zooarchaeological and Lithic Perspective - Real, Cristina (2018)
The Abrigo de la Quebrada (Chelva, Valencia) stratigraphic succession comprises nine Middle Palaeolithic levels. Human selection of this rock shelter for occupation owes to its favourable location—at the gates of a blind valley where the trapping of large herbivores would have been practicable. The immediate environment is varied, with both abrupt and flat terrain, and would have supported a wide range of prey animals. Radiocarbon-dated charcoal samples from level IV, which is characterised by a high density of lithic (> 18,000) and bone (> 100,000) remains, yielded results of 43,930 ± 750 BP (Beta-244002) and > 51,6 ka BP (OxA-24855). There is no evidence of modification by carnivores or birds of prey, so this level’s faunal remains must be anthropogenic in the main. Relative to the inhabited space, the location of level IV’s many combustion features shows little variation. The level’s typical palimpsest structure results from frequent, repeated occupations with intense on-site processing in a context of low sedimentation rates. The study of seasonality, carcass exploitation, taphonomy, stone tool refitting and raw material provenience patterns supports the notion that the different occupations subsumed in the level IV deposit were all short term. The comparison of our results with coeval contexts from the central area of Mediterranean Iberia sheds additional light on the adaptations of western Europe’s Neanderthal groups.